Babad tanah Djawa : gantjaran : kawiwitan saka Karaton Blambangan kang nunggal djaman karo Madjapahit tumeka Demak lan Padjang - Wirjapanitra (Toko Buku Sadu-Budi, 1945)
Historical legends and stories of the family trees and connection between kings and rulers of Jawa.